2019
DOI: 10.1152/japplphysiol.00379.2019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior alleviates thermal discomfort during steady-state exercise without affecting whole body heat loss

Abstract: We tested the hypothesis that thermal behavior resulting in reductions in mean skin temperature alleviates thermal discomfort and mitigates the rise in core temperature during light-intensity exercise. In a 27 ± 0°C, 48 ± 6% relative humidity environment, 12 healthy subjects (6 men, 6 women) completed 60 min of recumbent cycling. In both trials, subjects wore a water-perfused suit top continually perfusing 34 ± 0°C water. In the behavior trial, subjects maintained their upper body thermally comfortable by pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
1
13
1
Order By: Relevance
“…Visit one was the consent visit and visits two and three were experimental trials. Data from one of these experimental trials (i.e., the control trial) have been reported previously in a study that tested a different hypothesis [12]. The behavior trial in the current study was a completely separate trial from those presented previously in that subjects were restricted from behaving during exercise and only allowed to behave during recovery.…”
Section: Subjectsmentioning
confidence: 94%
See 3 more Smart Citations
“…Visit one was the consent visit and visits two and three were experimental trials. Data from one of these experimental trials (i.e., the control trial) have been reported previously in a study that tested a different hypothesis [12]. The behavior trial in the current study was a completely separate trial from those presented previously in that subjects were restricted from behaving during exercise and only allowed to behave during recovery.…”
Section: Subjectsmentioning
confidence: 94%
“…The distance of 6 mm was chosen because it ensured that the humidity sensor of the iButton would not become artificially supersaturated due to a droplet of sweat entering the hygrosensor [10,11]. Relative humidity from the iButtons and skin temperature from the adjacent thermocouple placed on each site were used to determine the water vapor pressure of the skin using standard calculations as previously reported [12,21]. Local skin wettedness was calculated according to the methods of Gagge [22] (See Appendix B).…”
Section: Instrumentation and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as heat production from active musculature increases, various neutrally mediated skin blood-flow and sweating reflexes occur in order to facilitate heat dissipation [3]. Despite these autonomic adjustments in order to serve cardiovascular and thermoregulatory functions, behavioural thermoregulation is still active during exercise and plays an important role in exercise intensity and local microclimate (i.e., seeking cooling and/or removing clothing) selection during exercise, ultimately to help limit thermal discomfort and avoid heat-related illness [4]. Furthermore, behavioural thermoregulation remains engaged after the cessation of exercise, which is particularly important due to the withdrawal of autonomic thermoeffectors [5] and the extended elevation of internal temperature and thermal discomfort post-exercise [6].…”
Section: Introductionmentioning
confidence: 99%